The study of dangers and countermeasures of fake news in social media - Xie, Yuting; Yasin, Megat Al Imran; Shekh Alsagoff, Syed Agil; Hoon, Ang Lay (2021)
Fake news as one of a normal phenomenon all over the world, it exertsa great impact on both individuals and our society. With the popularity of social media, fake news increasingly invades our lives, even brings disadvantages to institutions or countries. According to the analysis of several examples, the study aims to improve the phenomenon of fake news in social media so as to promise the authenticity of news in the field of media and communication. Even though it is difficult to achieve nowadays, especially in the current information era, in fact, it calls for the collective effort by the government, information producers and social media platform, as well as audiences. In addition, this study also expects to offer a reference to future journalism practitioners and related academic researchers.